The Story of the Vanished Project. Challenges and Coping Strategies in International Comparative and Collaborative Research Projects (Global Media Journal - German Edition, 2022)
The essay discusses the challenges that can occur in communication and media research projects with an international comparative and collaborative scope. The author uses her own research experience and auto-ethnographic reflections derived from an international comparative and collaborative media project to illustrate different considerations that researchers need to reflect upon in the implementation of such projects. The essay focuses not only on the “frontstage” of research projects (e.g., workplan, publications, presentations, established networks) but also sheds light on the “backstage” (Goffman), i.e., the project implementation, including conceptual, operational, interpretative, and social considerations, decisions, and procedures. It lists challenges that may arise and recommends conceptual, operational, interpretative, and social strategies that researchers may apply to confront them. The outlined experiences are not a rare phenomenon but are part of the “normal process and life cycle” of such projects. Researchers therefore should embrace them, reflect upon them, and acquire suitable coping strategies to assure a successful project implementation and knowledge production.
Keywords: International comparative research; international research collaboration; comparative research methodology; academic communication; scientific teamwork; team science; autoethnographic reflections